KELAYAKAN INVESTASI PUPUK SUNLAND CAIR ORGANIKDi PT ALOVE BALI DESA SABA, KECAMATAN BLAHBATUH, KABUPATEN GIANYAR - PRANANDA, NGAKAN NYOMAN GERI WIRA; USTRIYANA, I NYOMAN GEDE; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract The Investment Feasibility of Aloe Vera Liquid Organic Fertilizer at PT. Alove Bali at the Saba Village, Sub-District of Blahbatuh the Regency of Gianyar Bali. Aloevera is one of ten species of plants in the world that have the potential to be developed as a medicinal plant and industrial raw materials. As one of the producers of aloevera in Bali, Gianyar contained aloe vera processing plant into organic liquid fertilizer which is located in the village of Bonbiyu Blahbatuh named PT Alove Bali Ind. In this village most farmers cultivate aloe vera in the fields of marketing and moor land purchased by the factory.This study aimed to assess the feasibility of business investment Agribusiness organic liquid fertilizer made from aloevera is seen from the financial aspect, describing the agribusiness investment profile of organic liquid fertilizer in terms of technical aspects and, markets and marketing. The results of the feasibility study investment aloevera organic liquid fertilizer is financially feasible to do this business with the results of the Net Present Value (NPV) positive value of Rp 23.968.434.777 is greater than zero, the Internal Rate of Return (IRR) is greater than the real interest rate in the market 65,81% per year, Benefit. Cost Ratio of 4,45 (greater than one) and the results of payback period of 2,83 years. Thus, the investment feasibility of aloe vera organic liquid fertilizer PT Alove Bali is feasible. From the results of the sensitivity analysis shows that businesses that do still profitable and able to survive and meet the investment criteria despite the increased production cost. Key words : aloevera organic liquid fertilizer , Financial and Non Inancial Investment Criteria